Becoming Survived: Action to Eliminate Sexual Violence - Baby Jim Aditya (Jurnal Perempuan, 2016)
Sexual violence is an act of rape, sexual coercion, and harrasment, as well as sexual contact with coercion or threat using force. It is timely to consider that sexual violence is discussed in schools and take it as serious issue with empathy towards the victims and not only being considered as women’s issues that can only be discussed among women. Public awareness against it is crucial to be raised. This is important for women and girls as victim of violence to be survivors. These actions should also involve men in advocating against sexual violence. By providing an understanding of how men should behave toward women and listening to the testimony of women survivors of sexual violence of the trauma and its impact on women’s lives, it is expected that young men since early age will have a sensitivity in dealing with sexual violences.